2015
DOI: 10.5604/17322693.1142582
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of estrogens: benefit or risk

Abstract: Estrogens are widely used in hormone replacement therapy, gynecology, urogynecology and rarely in dermatology. Non-therapeutic use of estrogens is very widespread. Estrogens are used as contraceptives, which cause a lot of serious side effects. A common clinical problem is skin hyperpigmentation (melasma), occurring mainly in women who take contraceptives with high doses of estrogens. But low doses of estrogens may also cause skin side effects. The mechanism of melasma development is very complicated and not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hormone replacement therapy (HRT) had been reported to increase salivary secretion in postmenopausal women ( Yalçin et al, 2005 ; Lago et al, 2015 ). However, HRT possesses a risk of adverse side effects, including the development of endometrial and breast cancer ( Pietrzak et al, 2015 ). Phytoestrogens are plant-derived dietary compounds with structural similarity to E2 ( Rietjens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone replacement therapy (HRT) had been reported to increase salivary secretion in postmenopausal women ( Yalçin et al, 2005 ; Lago et al, 2015 ). However, HRT possesses a risk of adverse side effects, including the development of endometrial and breast cancer ( Pietrzak et al, 2015 ). Phytoestrogens are plant-derived dietary compounds with structural similarity to E2 ( Rietjens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis made using electron microscopy revealed that the skin affected by melasma shows an excessive amount of free pigment, as well as elastosis. Moreover, an increase in the expression of estrogen receptor is also noted . Pigment cells reveal increased metabolism.…”
Section: Introductionmentioning
confidence: 93%
“…Studies using diethylstilbestrol (DES) – a synthetic estrogen in mouse melanoma cells – have shown that DES stimulates pigment cells and induces melanogenesis …”
Section: Introductionmentioning
confidence: 99%